Refining Principles and Technical Methodologies to Produce Ultra-Pure Magnesium for High-Tech Applications - Seifeldin R. Mohamed; Semiramis Friedrich; Bernd Friedrich (Metals, 2019)
During the last decade, magnesium-based medical implants have become the focal point of a large number of scientific studies due to their perceived favorable properties. Implants manufactured from magnesium alloys are not only biocompatible and biodegradable, but they are also the answer to problems associated with other materials like stress shielding (Ti alloys) and low mechanical stability (polymers). Magnesium has also been a metal of interest in another field. By offering superior technical and economic features in comparison to lithium, it has received significant attention in recent years as a potential battery anode alternative. Natural abundancy, low cost, environmental friendliness, large volumetric capacity, and enhanced operational safety are among the reasons that magnesium anodes are the next breakthrough in battery development. Unfortunately, commercial production of such implants and primary and secondary cells has been hindered due to magnesium’s low corrosion resistance. Corrosion investigations have shown that this inferior quality is a direct result of the presence of certain impurities in metallic magnesium such as iron, copper, cobalt, and nickel, even at the lowest levels of concentration. Magnesium’s sensitivity to corrosion is an obstacle for its usage not only in biomedical implants and batteries, but also in the automotive/aerospace industries. Therefore, investigations focusing on magnesium refinement with the goal of producing high and ultra-high purity magnesium suitable for such demanding applications are imperative. In this paper, vacuum distillation fundamentals and techniques are thoroughly reviewed as the main refining principles for magnesium.